Genetic and Phenotype Analysis of a Chinese Cohort of Infants and Children With Epilepsy - Chuan, Zhang; Ruikun, Cai; Qian, Li; Shiyue, Mei; Shengju, Hao; Yong, Yuan; Haibo, Li; Neng, Xiao; Yong, Zhao; Huiqin, Xue; Weijia, Wang; Ling, Hui; et al. (Frontiers in Genetics, 2022)
Background: Epilepsy in childhood is a common and diverse neurological disorder. We conducted a genetic and phenotype analysis of a Chinese cohort of infants and children with epilepsy. Methods: We conducted a pedigree analysis of 260 Chinese patients with epilepsy onset during infancy or childhood by whole exome sequencing (WES). Results: Of the 260 probands analyzed, a genetic diagnosis was established in 135 patients. One-hundred eighty-eight phenotypes were detected in those 135 positive/likely positive patients, 106 patients had more than two phenotypes, and 67 patients had more than three phenotypes. A total of 142 variants of 81 genes were detected among the positive/likely positive patients. Among these 142 variants, of which 87 of 66 genes were novel. Conclusion: Our findings extend the variant spectrum of genes related to epilepsy. Our results will be useful for genetic testing and counseling for patients with epilepsy.